Dampak Perbedaan Pendapatan Pekerja Perempuan Sektor Informal di Desa Marga - Dian Anugrahita Dewi, I Gusti Ayu Made; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 1, Januari 2013 (pp. 1-62), 2012)
The aims of study were to discuss issues concerning the effect of the age, marital status, and education variable to earnings of women workers in simultaneously and partial in the informal sector of Marga village, and differences in the family income before and after the women working in the informal sector. This study was at Marga village. Number of sample was 100 people. The data analysis technique has been used were multiple linear regression and t test. The test results shows that the age, marital status, and education variable in simultaneous have significant effect on the informal sector women worker’s income. There are differences in family income before and after the women working.
Keywords: age; earning; education; marital status; women worker